Race and ethnicity of mothers with Spanish surnames - Oliveira, Carlos R. (J Public Health Epidemiol, 2013)
The objective of this study was to assess how hospital designation of race/ethnicity based on Spanish surnames of mothers correlated with the self-report, and explores how these mothers identified their own race/ethnicity using the National Institutes of Health (NIH) categories. 235 mothers were enrolled prospectively and asked to report their race/ethnicity. Positive predictive value (PPV) of using surnames as a tool for assigning race/ethnicity was determined. The PPV of using surnames to identify ethnicity and race was 79 and 30%, respectively. 57% of mothers could not identify their race by the NIH categories. Although Spanish surnames more accurately reflected ethnicity than race, its use was associated with substantial discrepancies.